Associations between plasma neurofilament light, in vivo brain pathology, and cognition in non‐demented individuals with autosomal‐dominant Alzheimer's disease. Issue 5 (1st February 2021) - Guzmán‐Vélez, Edmarie; Zetterberg, Henrik; Fox‐Fuller, Joshua T.; Vila‐Castelar, Clara; Sanchez, Justin S.; Baena, Ana; Garcia‐Ospina, Gloria; Aguillon, David; Pardilla‐Delgado, Enmanuelle; Gatchel, Jennifer R.; Sperling, Reisa A.; Johnson, Keith; et al.
Abstract: Background: Neurofilament light (NfL) is a promising biomarker of early neurodegeneration in Alzheimer's disease (AD). We examined whether plasma NfL was associated with in vivo amyloid beta and tau, and cognitive performance in non‐demented presenilin‐1 ( PSEN1 ) E280A mutation carriers. Methods: Twenty‐five mutation carriers and 19 non‐carriers (age range: 28 to 49 years) were included in this study. Participants underwent 11C Pittsburgh compound B (PiB)‐PET (positron emission tomography), flortaucipir–PET, blood sampling, and cognitive testing. Results: Mutation carriers exhibited higher plasma NfL levels than non‐carriers. In carriers, higher NfL levels were related to greater regional tau burden and worse cognition, but not amyloid beta load. When we adjusted for age, a proxy of disease progression, elevated plasma NfL levels were only correlated with worse memory recall. Conclusions: Findings support an association between plasma NfL, cognition, and tau pathology in non‐demented individuals at genetic risk for developing AD dementia. Plasma NfL may be useful for selecting individuals at increased risk and tracking disease progression in AD.